Dampak Covid-19 terhadap Pariwisata Bali Ditinjau dari Sektor Sosial, Ekonomi, dan Lingkungan (Sebuah Tinjauan Pustaka) - A.A.A Ribeka Martha Purwahita; Putu Bagus Wisnu Wardhana; I Ketut Ardiasa; I Made Winia (LEMBAGA PENELITIAN DAN PENGABDIAN KEPADA MASYARAKAT AKADEMI PARIWISATA DENPASAR, 2021)
The impact of covid-19 has had a huge impact in various sectors, especially for tourism actors and businesses, especially since Bali relies heavily on the tourism sector. In writing in the form of a literature review, it is further described the problems that arise and the impact of developments in the social, economic and environmental sectors during the Covid-19 pandemic by identifying the global covid-19 outbreak which immediately affects the development of tourism in Bali. In accordance with the Bali Provincial Regulation No. 2 of 2012, Bali tourism is based on culture that is able to drive tourism potential in the dynamics of local, national and global life. Currently the development of tourism in Bali has decreased drastically even to minus since 2020, which has paralyzed various sectors, especially in the economic sector, especially in the tourism business sector as well as in the employment sector which can be seen in layoffs (PHK) and the closure of tourism businesses due to the decline. requests from tourists. In the social sector, it can be seen from the behavior and habits of the community, tourism actors and tourists. Rules from the government to be implemented in the community in accordance with the prevention of the spread of covid-19 are more widely known as 3M (washing hands, wearing masks, maintaining distance) and CHSE (cleanliness, healthy, safety and environment) which includes a program for implementing health protocols. The environmental sector, which has an impact on the pandemic situation, has had a positive impact, given that the excessive and excessive exploitation of nature can now be minimized and reduced. Pollution caused by economic activity is also reduced, thus improving air quality and the environment. Seeing this condition, the government plays an important role in issuing policies for the community and the tourism component (stakeholders) so that they can remain active and productive in movements in the economic sector. In the tourism sector, government policies are urgently needed and can be realized immediately in the hope that tourism conditions will gradually recover.